An improved algorithm for digital impedance relays simulation and experiment - Chen, Jingke (1987)
This thesis presents an improved algorithm for digital impedance relays of long-transmission-lines. The algorithm has a higher ability to process transient signals and needs a narrower data window compared to other algorithms. For the first step, the analytical of solving for the electromagnetic transients on a distributed transmission system is introduced. This is a key step because it reveals the natural characteristics of transient signals on distributed systems and its results enable us to develop an improved algorithm. Secondly, as an application, the natural characteristics of transient signals is used as a basis for the Least-Squares approach to create an improved algorithm. The algorithm for the impedance relay is simply like a FIR digital filter, but the differences are that it it designed especially for processing transient signals and by a time-domain approach design method. As a result, the algorithm for the digital impedance relay does not need any filter to pre-process inout signals. The Nyquist Sampling Theory is easily satisfied when a new definition named time-variance spectrum is introduced into spectrum analysis. Thirdly, the system simulation is adopted for checking the improved algorithm by applying it to a distributed transmission system and comparing it with the umimproved one. Lastly, the algorithm is realized on a Z80 microprocessor and the dynamic tests are completed on a transmission line model.